2018
DOI: 10.5614/jrcp.2018.29.1.1
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Level of Development in Malang Regency Based on a Typology of Development Regions

Abstract: A regionalization approach seeks to manage and to achieve development goals in line with regional characteristics. The development system of Malang Regency is conducted through regionalization approach that divided the area into six development regions (DR). Considering that each region has diverse characteristics/typology, describing this typology is the key to map the conditions and problems and to formulate alternative solutions. Thus, the main objective of the research is to analyze the development level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The average value of PEK was 22.94, which means that Bulukumba Regency has an economic potential to develop going forward because it is supported by the potential of many available natural resources that have not been managed. A national development approach that greatly emphasizes macroeconomic growth tends to ignore the great inter-regional development inequality that exists [69]. Furthermore, the shift from a traditional economy to a circular economy requires the realization of environmental innovations and sustainable engineering solutions [70].…”
Section: Shift-share Analysismentioning
confidence: 99%
“…The average value of PEK was 22.94, which means that Bulukumba Regency has an economic potential to develop going forward because it is supported by the potential of many available natural resources that have not been managed. A national development approach that greatly emphasizes macroeconomic growth tends to ignore the great inter-regional development inequality that exists [69]. Furthermore, the shift from a traditional economy to a circular economy requires the realization of environmental innovations and sustainable engineering solutions [70].…”
Section: Shift-share Analysismentioning
confidence: 99%
“…A variety of research approaches are used in the classification of regional units, for instance, the affinity propagation method proposed by Fiaschetti et al (2021). Data mining methods, such as k-means or Ward's algorithm and other cluster analysis algorithms are relatively often used with regional typologies (Hedlund, 2016;Latuconsina et al, 2018). Many authors apply also Linear Discriminant Analysis (LDA) (Jaba et al, 2006;Bat贸g and Bat贸g, 2019;El-Hanjouri and Hamad, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Such disparities may become a barrier to maintaining the dynamic development of the whole country or the specific region (Adamowicz and Pyra, 2019). Measurement of regional socio-economic performance and identification of regional typologies play a crucial role in research as well as in policy-making when proper typology of regions allows to allocate resources across heterogeneous spaces and define policy priorities (Greco et al, 2018;Latuconsina et al, 2018). According to Bajracharya and Hastings (2018), identification of regional growth patterns and economic development are key attributes of a framework that has generally resulted in acceptable regional outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in economic growth of the three urban areas is largely determined by factors of economic activity based on spatial scale, service systems and demand for goods and services. A national development approach that greatly emphasizes macroeconomic growth tends to ignore the great inter-regional development inequality that exists [105]. Thus, it can be concluded that economic growth is a determining factor for spatial interactions toward the distribution patterns of the flow of goods and services, scale of services and urban population.…”
Section: Urban Agglomeration and Economic Growthmentioning
confidence: 99%